Location and classification of Canalis sinuosus for cone beam computed tomography: avoiding misdiagnosis - Luiz Roberto Coutinho MANHÃES JÚNIOR; Maria Fernanda Lima VILLAÇA-CARVALHO; Mari Eli Leonelli MORAES; Sérgio Lúcio Pereira de Castro LOPES; Milena Bortolotto Felippe SILVA; José Luiz Cintra JUNQUEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study was to assess the presence, location and, multiplanar distance of the canalis sinuosus (CS) between the incisive foramen and the anterior maxillary alveolar ridge using cone beam computed tomography (CBCT). Therefore, 500 CBCT maxillary images obtained from male and female patients aged 20 to 80 years were selected to assist in the dental treatment. Low-quality tomographic images were discarded. All images were captured with the i-CATTM Classic tomograph and assessed using the XoranCatTM software. The axial sections were analyzed at the incisive foramen in order to verify the CS presence in laterality and location. Furthermore, linear measurements of the nasal cavity floor, buccal cortical bone, and alveolar ridge crest were made. All the collected data were statistically analyzed. Results show a variation of the CS in relation to the classification and distance of anatomical structures, but no significant difference between the right and left sides. It should be highlighted that CBCT is necessary before invasive procedures in order to preserve important anatomical structures. In conclusion, the location of the CS varies in relation to the alveolar ridge crest and buccal cortical bone, assuming that it is going to be located by the upper lateral incisor palatine.